Effects of total astragalosides on cardiomyocyte apoptosis and mitochondrial membrane potential in rats with heart failure - YOU Xu, ZHU Xiao-fang, HU Yun-peng, GONG Yang, ZHAO Lei (Jichu yixue yu linchuang, 2020)
Objective To study the effect and mechanism of total astragalosides(ASTs) on myocardial cell apoptosis and mitochondrial membrane potential in rats with heart failure. Methods Rats were divided into control group(normal), heart failure group(model), AST low, medium and high intervention group (10, 20 and 40 mg/kg intragastric administration) and 12 rats in each group. Cardiac function was measured in rats. Myocardial tissue was taken from rats, apoptosis was detected by TUNEL assay, the activity of SOD was detected by xanthine oxidze method, the activity of GSH-PX was determined by dithio-dinitromethylbenzene method, MDA content was determined by thiobarbituric acid method, the mitochondrial membrane potential was measured by JC-1 method. Western blot was used to detect the expression levels of c-caspase-3, c-caspase-9, p-AKT, p-p38MAPK and Cyt-C in mitochondria and cytoplasm. Results Compared with normal group, LVSP,+dp/dtmax,-dp/dtmax in model group decreased(P＜0.05),the apoptotic rate and the level of c-caspase-3 and c-caspase-9 protein increased(P＜0.05), the activities of SOD and GSH-PX decreased(P＜0.05), the content of MDA increased(P＜0.05), the mitochondrial membrane potential decreased(P＜0.05), the level of Cyt-C protein in mitochondria decreased(P＜0.05), Cyt-c protein level in cytoplasm increased(P＜0.05), the level of p-AKT decreased, the level of p-p38MAPK increased(P＜0.05). Compared with model group, LVSP, +dp/dtmax,-dp/dtmax increased in AST-L, AST-M and AST-H groups, the apoptotic rate and c-caspase-3,c-caspase-9 protein levels decreased, the activities of SOD and GSH-PX increased, the content of MDA decreased, the mitochondrial membrane potential increased, the level of Cyt-C protein in mitochondria increased, Cyt-c protein level in cytoplasm decreased, the level of p-AKT increased, the level of p-p38 MAPK decreased, the higher the concentration of total astragalosides is, the greater the effect on heart failure rat model. Conclusions Total astragalosides inhibit cardiomyocyte apoptosis in rats with heart failure. The mechanism may be related to the increase of mitochondrial membrane potential and the influence of AKT and p38MAPK signaling pathways.